An electrolyte and a battery comprising the same

CN116093429BActive Publication Date: 2026-10-23ZHUHAI COSMX BATTERY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211098343.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-08
Publication Date
2026-10-23
Estimated Expiration
2042-09-08

AI Technical Summary

Benefits of technology

[0064] This invention provides an electrolyte and a battery including the electrolyte. The invention employs a combination of ethyl propionate solvent and a silane compound, vinyl sulfate, and lithium difluorophosphate. When the silane compound is used alone, it can form a protective film on the positive electrode, but this protective film has high impedance and low ionic conductivity. When the silane compound, vinyl sulfate, and lithium difluorophosphate are used together, the three can work together to form a composite interface protective film on both the positive and negative electrode surfaces. This composite interface protective film is robust, has low impedance, and exhibits high ionic conductivity. Combined with the low-viscosity ethyl propionate solvent, the conductivity of the electrolyte can be further improved. Simultaneously, this composite interface protective film can also improve the interfacial compatibility between the electrode and the electrolyte, effectively suppressing side reactions between the electrode and the electrolyte, improving the battery's safety performance (enabling the battery to simultaneously meet thermal shock, overcharge, and nail penetration requirements), and also improving the battery's low-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0003839396930000021
    Figure BDA0003839396930000021
Patent Text Reader

Abstract

The application provides an electrolyte and a battery comprising the electrolyte, and adopts a combination of an ethyl propionate solvent and a combination of a silanecarbonitrile compound, ethylene sulfate and lithium difluorophosphate; wherein, when the silanecarbonitrile compound is used alone, a protective film can be formed on the positive electrode, but the impedance of the protective film is relatively large and the ionic conductivity is relatively low; when the silanecarbonitrile compound, the ethylene sulfate and the lithium difluorophosphate are combined, the three can jointly act and form a composite interface protective film on the surfaces of the positive and negative electrodes, the composite interface protective film is relatively firm and has relatively low impedance, and simultaneously has the characteristics of high ionic conductivity, and the combination of the ethyl propionate solvent with relatively low viscosity can further improve the conductivity of the electrolyte; meanwhile, the composite interface protective film can also improve the interface compatibility of the electrode and the electrolyte, effectively inhibits the side reaction between the electrode and the electrolyte, improves the safety performance of the battery and also improves the low-temperature performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to an electrolyte with high safety and low-temperature performance, and a battery including the electrolyte. Background Technology

[0002] Since their commercialization, lithium-ion batteries have been widely used in digital, energy storage, power, military, aerospace, and communication equipment due to their high specific energy and good cycle performance. With the widespread application of lithium-ion batteries, consumers' demands for their performance in various environments are constantly increasing, requiring lithium-ion batteries to have characteristics that balance high and low temperature performance. At the same time, lithium-ion batteries have serious safety issues during use. Overcharging, over-discharging, or extreme usage conditions can easily lead to safety hazards, such as fires or even explosions.

[0003] Electrolyte, as a crucial component of lithium-ion batteries, significantly impacts battery performance. To address the aforementioned issues, adding overcharge protection additives to the electrolyte can improve safety performance. However, these additives have limited ability to suppress overcharging when used in small amounts, while excessive amounts can lead to severe degradation of the battery's low-temperature performance. Therefore, developing lithium-ion battery electrolytes that provide safety protection without compromising the battery's low-temperature performance is urgently needed. Summary of the Invention

[0004] The purpose of this invention is to solve the safety problems of existing lithium-ion batteries caused by overcharging, over-discharging and / or high-temperature storage, and to provide an electrolyte with high safety performance and a battery including the electrolyte. The battery has excellent safety performance (capable of thermal shock resistance, overcharge resistance and nail penetration resistance) and low-temperature performance.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] An electrolyte comprising an organic solvent, an additive, and an electrolyte salt, wherein the organic solvent comprises ethyl propionate; and the additive comprises a first additive selected from silicone compounds, vinyl sulfate, and lithium difluorophosphate.

[0007] According to an embodiment of the present invention, the silane compound is a compound containing at least one -Si(CN)3 functional group; preferably, the silane compound is a compound containing two -Si(CN)3 functional groups.

[0008] According to an embodiment of the present invention, the silanenitrile compound is selected from at least one of the compounds shown in Formula 1:

[0009]

[0010] In Formula 1, R1 is selected from substituted or unsubstituted alkylene groups; if substituted, the substituent is a halogen or alkyl group.

[0011] According to an embodiment of the present invention, in Formula 1, R1 is selected from substituted or unsubstituted C. 1-9 Alkylene; if substituted, the substituent is a halogen or C. 1-9 alkyl.

[0012] According to an embodiment of the present invention, in Formula 1, R1 is selected from substituted or unsubstituted C. 3-7 Alkylene; if substituted, the substituent is a halogen or C. 1-3 alkyl.

[0013] According to an embodiment of the present invention, the silanenitrile compound is selected from at least one of the compounds shown in A1 to A6 below:

[0014]

[0015]

[0016] According to embodiments of the present invention, the content of the silane compound as a percentage of the total mass of the electrolyte is 0.2wt% to 6wt%, for example, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.2wt%, 1.3wt%, 1.5wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.8wt%, 3wt%, 3.3wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, 5wt%, 5.2wt%, 5.5wt%, or 6wt%.

[0017] According to an embodiment of the present invention, the content of the vinyl sulfate as a percentage of the total mass of the electrolyte is 0.2wt% to 1.5wt%, for example, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.2wt%, 1.3wt%, or 1.5wt%.

[0018] According to an embodiment of the present invention, the lithium difluorophosphate content accounts for 0.1 wt% to 1 wt% of the total mass of the electrolyte, for example, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, or 1 wt%.

[0019] According to an embodiment of the present invention, the content of ethyl propionate as a percentage of the total mass of the electrolyte is 5 wt% to 70 wt%, for example, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, or 70 wt%.

[0020] According to an embodiment of the present invention, the additive further includes a second additive, the second additive being selected from trifluoromethyl-substituted ether compounds and / or trifluoromethyl-substituted epoxide alkane compounds.

[0021] According to an embodiment of the present invention, the content of the second additive as a percentage of the total mass of the electrolyte is 0.2wt% to 5wt%, for example, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.2wt%, 1.3wt%, 1.5wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.8wt%, 3wt%, 3.3wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt%, or 5wt%.

[0022] According to embodiments of the present invention, the trifluoromethyl-substituted ether compound is selected from at least one compound of Formula 2 and / or at least one compound of Formula 3:

[0023] R2-O-R3-C(CF3) n (H) m Formula 2

[0024]

[0025] In Formula 2, R2 is a substituted or unsubstituted alkyl group; if substituted, the substituent is an alkyl, alkoxy, or halogen; R3 is an alkylene group that is absent, substituted, or unsubstituted; if substituted, the substituent is an alkyl, alkoxy, or halogen; n is an integer between 1 and 3, m is an integer between 0 and 2, and n+m=3;

[0026] In Formula 3, R4 and R5 may be the same or different, and are independently selected from substituted or unsubstituted alkyl, substituted or unsubstituted alkoxy groups; if substituted, the substituents are alkyl, alkoxy or halogen.

[0027] R6 and R7 may be the same or different, and are independently selected from hydrogen, trifluoromethyl, substituted or unsubstituted alkyl, substituted or unsubstituted alkoxy, and R6 and R7 contain at least one trifluoromethyl group; if substituted, the substituent is alkyl, alkoxy or halogen.

[0028] According to an embodiment of the present invention, in formula 2, R2 is substituted or unsubstituted C. 1-12 Alkyl group; if substituted, the substituent is C. 1-12 Alkyl, C 1-12 alkoxy or halogen; R3 is a C that is absent, substituted, or unsubstituted. 1-12 Alkylene; if substituted, the substituent is C. 1-12 Alkyl, C 1-12 Alkyl or halogen; n is an integer between 1 and 3, m is an integer between 0 and 2, and n+m=3.

[0029] According to an embodiment of the present invention, in formula 3, R4 and R5 may be the same or different, and are independently selected from substituted or unsubstituted C. 1-12 Alkyl, substituted or unsubstituted C 1-12 alkoxy group; if substituted, the substituent is C. 1-12 Alkyl, C 1-12 Alkoxy or halogen;

[0030] R6 and R7 may be the same or different, and are independently selected from hydrogen, trifluoromethyl, substituted or unsubstituted C. 1-12 Alkyl, substituted or unsubstituted C 1-12 The alkoxy group, and R6 and R7 contain at least one trifluoromethyl group; if substituted, the substituent is C. 1-12 Alkyl, C 1-12 Alkoxy or halogen.

[0031] According to an embodiment of the present invention, in formula 2, R2 is substituted or unsubstituted C. 1-6 Alkyl group; if substituted, the substituent is C. 1-6 Alkyl, C 1-6 alkoxy or halogen; R3 is a C that is absent, substituted, or unsubstituted. 1-6 Alkylene; if substituted, the substituent is C. 1-6 Alkyl, C 1-6 Alkyl or halogen; n is an integer between 1 and 3, m is an integer between 0 and 2, and n+m=3.

[0032] According to an embodiment of the present invention, in formula 3, R4 and R5 may be the same or different, and are independently selected from substituted or unsubstituted C. 1-6 Alkyl, substituted or unsubstituted C 1-6 alkoxy group; if substituted, the substituent is C. 1-6 Alkyl, C1-6 Alkoxy or halogen;

[0033] R6 and R7 may be the same or different, and are independently selected from hydrogen, trifluoromethyl, substituted or unsubstituted C. 1-6 Alkyl, substituted or unsubstituted C 1-6 The alkoxy group, and R6 and R7 contain at least one trifluoromethyl group; if substituted, the substituent is C. 1-6 Alkyl, C 1-6 Alkoxy or halogen.

[0034] According to an embodiment of the present invention, in formula 2, R2 is substituted or unsubstituted C. 1-3 Alkyl group; if substituted, the substituent is C. 1-3 Alkyl, C 1-3 alkoxy or halogen; R3 is a C that is absent, substituted, or unsubstituted. 1-3 Alkylene; if substituted, the substituent is C. 1-3 Alkyl, C 1-3 Alkyl or halogen; n is an integer between 2 and 3, m is an integer between 0 and 1, and n+m=3.

[0035] According to an embodiment of the present invention, in formula 3, R4 and R5 may be the same or different, and are independently selected from substituted or unsubstituted C. 1-3 Alkyl, substituted or unsubstituted C 1-3 alkoxy group; if substituted, the substituent is C. 1-3 Alkyl, C 1-3 Alkoxy or halogen;

[0036] R6 and R7 may be the same or different, and are independently selected from hydrogen, trifluoromethyl, substituted or unsubstituted C. 1-3 Alkyl, substituted or unsubstituted C 1-3 The alkoxy group, and R6 and R7 contain at least one trifluoromethyl group; if substituted, the substituent is C. 1-3 Alkyl, C 1-3 Alkoxy or halogen.

[0037] According to embodiments of the present invention, the trifluoromethyl-substituted ether compound is selected from at least one of the compounds shown in B1 to B6 below:

[0038]

[0039] According to an embodiment of the present invention, the trifluoromethyl-substituted epoxide alkane compound is selected from compounds shown in Formula 4 below:

[0040] R8-CF3 Formula 4

[0041] In Equation 4, R8 is selected from substituted or unsubstituted C. 3-10Epoxyalkyl; if substituted, the substituent is halogen or C. 1-12 alkyl.

[0042] According to an embodiment of the present invention, R8 is selected from substituted or unsubstituted C. 3-6 Epoxyalkyl; if substituted, the substituent is halogen or C. 1-6 alkyl.

[0043] According to an embodiment of the present invention, R8 is selected from substituted or unsubstituted C. 3-4 Epoxyalkyl; if substituted, the substituent is halogen or C. 1-3 alkyl.

[0044] According to an embodiment of the present invention, the trifluoromethyl-substituted epoxide alkane compound is selected from at least one of the compounds shown in B7 to B8 below:

[0045]

[0046] According to embodiments of the present invention, the organic solvent further includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, propyl propionate, and propyl acetate.

[0047] According to an embodiment of the present invention, the electrolyte comprises an electrolyte lithium salt, wherein the electrolyte lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium hexafluorophosphate.

[0048] According to an embodiment of the present invention, the content of the electrolyte salt as a percentage of the total mass of the electrolyte is 13wt% to 20wt%, for example, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, or 20wt%.

[0049] According to an embodiment of the present invention, the additive further includes a third additive, which is selected from at least one of fluoroethylene carbonate and 1,3-propenesulfonate lactone.

[0050] The present invention also provides a battery comprising the electrolyte described above.

[0051] According to an embodiment of the present invention, the battery is a lithium-ion battery.

[0052] According to an embodiment of the present invention, the battery further includes a positive electrode, a negative electrode, and a separator.

[0053] According to an embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active material layer coated on one or both surfaces of the positive current collector, wherein the positive active material layer includes a positive active material, a conductive agent, and a binder.

[0054] According to an embodiment of the present invention, the positive electrode active material is selected from lithium cobalt oxide or lithium cobalt oxide doped with two or more elements selected from Al, Mg, Mn, Cr, Ti, and Zr, wherein the lithium cobalt oxide doped with two or more elements selected from Al, Mg, Mn, Cr, Ti, and Zr has the chemical formula Li. x Co 1-y1-y2-y3-y4 A y1 B y2 C y3 D y4 O2; 0.95≤x≤1.05, 0.01≤y1≤0.1, 0.01≤y2≤0.1, 0≤y3≤0.1, 0≤y4≤0.1, A, B, C, and D are selected from two or more elements among Al, Mg, Mn, Cr, Ti, and Zr.

[0055] According to an embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one or both surfaces of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder.

[0056] According to an embodiment of the present invention, the negative electrode active material is selected from graphite; it also optionally contains SiOx / C or Si / C, wherein 0 <x<2。

[0057] According to an embodiment of the present invention, the mass percentage of each component in the positive electrode active material layer is: 80-99.8 wt% positive electrode active material, 0.1-10 wt% conductive agent, and 0.1-10 wt% binder.

[0058] Preferably, the mass percentage of each component in the positive electrode active material layer is: 90-99.6 wt% positive electrode active material, 0.2-5 wt% conductive agent, and 0.2-5 wt% binder.

[0059] According to an embodiment of the present invention, the mass percentage of each component in the negative electrode active material layer is: 80-99.8 wt% negative electrode active material, 0.1-10 wt% conductive agent, and 0.1-10 wt% binder.

[0060] Preferably, the mass percentage of each component in the negative electrode active material layer is: 90-99.6 wt% negative electrode active material, 0.2-5 wt% conductive agent, and 0.2-5 wt% binder.

[0061] According to an embodiment of the present invention, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.

[0062] According to an embodiment of the present invention, the adhesive is selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.

[0063] The beneficial effects of this invention are:

[0064] This invention provides an electrolyte and a battery including the electrolyte. The invention employs a combination of ethyl propionate solvent and a silane compound, vinyl sulfate, and lithium difluorophosphate. When the silane compound is used alone, it can form a protective film on the positive electrode, but this protective film has high impedance and low ionic conductivity. When the silane compound, vinyl sulfate, and lithium difluorophosphate are used together, the three can work together to form a composite interface protective film on both the positive and negative electrode surfaces. This composite interface protective film is robust, has low impedance, and exhibits high ionic conductivity. Combined with the low-viscosity ethyl propionate solvent, the conductivity of the electrolyte can be further improved. Simultaneously, this composite interface protective film can also improve the interfacial compatibility between the electrode and the electrolyte, effectively suppressing side reactions between the electrode and the electrolyte, improving the battery's safety performance (enabling the battery to simultaneously meet thermal shock, overcharge, and nail penetration requirements), and also improving the battery's low-temperature performance.

[0065] Building upon this, the further introduction of a second additive (trifluoromethyl-substituted ether compounds and / or trifluoromethyl-substituted epoxide alkane compounds) can enhance the synergistic effect among the additives in the electrolyte. When it works together with the first additive and ethyl propionate, it can generate a high-strength composite interfacial protective film on the positive electrode surface. Since trifluoromethyl is an electron-withdrawing functional group, it has higher oxidation stability, which can improve the high-voltage resistance of the electrolyte and promote the Li... + The solvation of the electrolyte alters the solvated sheath, resulting in a higher lithium-ion transference number. It also improves the conductivity of the electrolyte, enhances the low-temperature performance of the battery, and significantly improves the electrochemical stability of the electrolyte. This makes the electrolyte more resistant to high voltage and less flammable, further improving the safety performance of the battery. Detailed Implementation

[0066] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0067] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0068] Comparative Examples 1-4 and Examples 1-10

[0069] The lithium-ion batteries of Comparative Examples 1-4 and Examples 1-10 were all prepared according to the following preparation method, with the only difference being the selection and amount of solvent and additives. The specific differences are shown in Table 1.

[0070] (1) Preparation of positive electrode

[0071] The positive electrode active material LiCoO2, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black were mixed in a weight ratio of 97:2:1. N-methylpyrrolidone (NMP) was added, and the mixture was stirred under vacuum until a uniform and fluid positive electrode slurry was formed. The positive electrode slurry was uniformly coated onto an aluminum foil with a thickness of 9–12 μm. The coated aluminum foil was baked in an oven with five different temperature gradients, and then dried in an oven at 120°C for 8 hours. Finally, it was rolled and slit to obtain the desired positive electrode sheet.

[0072] (2) Preparation of negative electrode sheet

[0073] A slurry was prepared by wet process using artificial graphite anode material (96.5% by weight), single-walled carbon nanotube (SWCNT) conductive agent (0.2% by weight), conductive carbon black (SP) conductive agent (1% by weight), sodium carboxymethyl cellulose (CMC) binder (1% by weight), and styrene-butadiene rubber (SBR) binder (1.3% by weight). The slurry was coated on the surface of copper foil for the anode current collector, and then dried (temperature: 85℃, time: 5h), rolled, and die-cut to obtain the anode sheet.

[0074] (3) Electrolyte preparation

[0075] In an argon-filled glove box (moisture <10ppm, oxygen <1ppm), ethylene carbonate (EC), propylene carbonate (PC), and propyl propionate (PP) were mixed uniformly in a mass ratio of 1:1:3. Then, 14 wt.% LiPF6, 5 wt.% fluoroethylene carbonate, 3 wt.% 1,3-propenesulfonate lactone, additives (silicone compounds, vinyl sulfate, lithium difluorophosphate, trifluoromethyl-substituted ether compounds and / or trifluoromethyl-substituted epoxide compounds), and ethyl propionate (the specific amounts and selections of additives and ethyl propionate are shown in Table 1) were slowly added to the mixed solution and stirred until homogeneous to obtain the electrolyte.

[0076] (4) Preparation of the diaphragm

[0077] A 2μm thick composite layer of titanium dioxide and polyvinylidene fluoride-hexafluoropropylene copolymer was coated onto a 5μm thick polyethylene diaphragm.

[0078] (5) Preparation of lithium-ion batteries

[0079] The prepared positive electrode sheet, separator, and negative electrode sheet are wound to obtain a bare cell without electrolyte injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum sealing, standing, formation, shaping, and sorting, the desired lithium-ion battery is obtained.

[0080] Table 1. Composition of the electrolytes for lithium-ion batteries prepared in Comparative Examples 1-4 and Examples 1-10

[0081]

[0082] The electrochemical performance of the lithium-ion batteries obtained in the comparative examples and embodiments described above was tested, and the results are as follows:

[0083] (1) 0℃ Cyclic Experiment: The batteries obtained in the above examples and comparative examples were placed in an environment of (0±2)℃ and left to stand for 2-3 hours. When the battery body reached (0±2)℃, the battery was charged at a constant current of 0.5C with a cutoff current of 0.05C. After the battery was fully charged, it was left to stand for 5 minutes, and then discharged at a constant current of 0.5C to the cutoff voltage of 3.0V. The highest discharge capacity of the first 3 cycles was recorded as the initial capacity Q. When the required number of cycles was reached, the discharge capacity Q1 of the last cycle of the battery was recorded. The results are shown in Table 2.

[0084] The calculation formula used is as follows: Capacity retention rate (%) = Q1 / Q × 100%.

[0085] (2) Low-temperature discharge experiment: The batteries obtained in the above examples and comparative examples were discharged at 0.2C to 3.0V at an ambient temperature of (25±3)℃, and then left to rest for 5 minutes. Then they were charged at 0.7C. When the cell terminal voltage reached the charging limit voltage, constant voltage charging was switched until the charging current was less than or equal to the cutoff current. Charging was stopped, and the batteries were left to rest for 5 minutes. Then they were discharged at 0.2C to 3.0V. The discharge capacity was recorded as the room temperature capacity Q2. Then the cells were charged at 0.7C. When the cell terminal voltage reached the charging limit voltage, constant voltage charging was switched until the charging current was less than or equal to the cutoff current. The fully charged batteries were left to rest at (-10±2)℃ for 4 hours. Then they were discharged at 0.2C to the cutoff voltage of 3.0V. The discharge capacity Q3 was recorded. The low-temperature discharge capacity retention rate was calculated. The results are shown in Table 2.

[0086] Low-temperature discharge capacity retention rate of the battery (%) = Q3 / Q2 × 100%.

[0087] (3) 135℃ thermal shock test: The batteries obtained in the above examples and comparative examples were heated at an initial temperature of (25±3)℃ using convection or a circulating hot air chamber, with a temperature change rate of (5±2)℃ / min. The temperature was increased to (135±2)℃ and held for 60min before the test was ended. The battery status results are recorded as shown in Table 2.

[0088] (4) Overcharge test: The batteries obtained in the above examples and comparative examples were charged to 5V at a constant current of 3C and the battery status was recorded. The results are shown in Table 2.

[0089] (5) Needle penetration test: Using a high-temperature resistant steel needle with a diameter of ф5-8mm (the cone angle of the needle tip is 45℃-60℃, and the surface of the needle is smooth and free of rust, oxide layer and oil), the batteries obtained in the above examples and comparative examples are penetrated from a direction perpendicular to the battery plates at a speed of (25±5)mm / s. The penetration position should be close to the geometric center of the pierced surface (the steel needle stays in the battery). When the battery surface temperature drops to the peak temperature of 10℃ or below after 1 hour, the test is stopped and the battery status is recorded. The results are shown in Table 2.

[0090] Table 2 shows the battery test results obtained from Comparative Examples 1-4 and Examples 1-10.

[0091]

[0092] As can be seen from the results in Table 2, the comparative examples and embodiments show that the present invention, by adding ethyl propionate solvent, silane compounds, ethylene sulfate, and lithium difluorophosphate to the electrolyte, can significantly improve the safety performance of lithium-ion batteries through synergistic effects, while also enabling the batteries to have good low-temperature performance.

[0093] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A battery, the battery comprising an electrolyte, characterized in that, The electrolyte comprises an organic solvent, additives, and an electrolyte salt. The organic solvent includes ethyl propionate. The additives consist of a first additive, a second additive, and a third additive; or the additives consist of a first additive and a second additive. The first additive is a silane nitrile compound, vinyl sulfate, and lithium difluorophosphate. The second additive is selected from trifluoromethyl-substituted ether compounds and / or trifluoromethyl-substituted epoxide compounds. The third additive is fluoroethylene carbonate and 1,3-propenesulfonate lactone. The silane compound is selected from at least one of the compounds shown in Formula 1: Formula 1 In Formula 1, R1 is selected from substituted or unsubstituted alkylene groups; if substituted, the substituent is a halogen or alkyl group. The content of the silane compound is 0.2wt%~6wt% of the total mass of the electrolyte; The content of the vinyl sulfate is 0.2wt%~1.5wt% of the total mass of the electrolyte; The lithium difluorophosphate content accounts for 0.1 wt% to 1 wt% of the total mass of the electrolyte. The content of ethyl propionate is 5wt% to 70wt% of the total mass of the electrolyte.

2. The battery according to claim 1, characterized in that, The content of the second additive is 0.2wt% to 5wt% of the total mass of the electrolyte.

3. The battery according to claim 1, characterized in that, The trifluoromethyl-substituted ether compounds are selected from at least one compound of Formula 2 and / or at least one compound of Formula 3: R2-O-R3-C(CF3) n (H) m Formula 2 Formula 3 In Formula 2, R2 is a substituted or unsubstituted alkyl group; if substituted, the substituent is an alkyl, alkoxy, or halogen; R3 is an alkylene group that is absent, substituted, or unsubstituted; if substituted, the substituent is an alkyl, alkoxy, or halogen; n is an integer between 1 and 3, m is an integer between 0 and 2, and n+m=3; In Formula 3, R4 and R5 may be the same or different, and are independently selected from substituted or unsubstituted alkyl, substituted or unsubstituted alkoxy groups; if substituted, the substituents are alkyl, alkoxy or halogen. R6 and R7 may be the same or different, and are independently selected from hydrogen, trifluoromethyl, substituted or unsubstituted alkyl, substituted or unsubstituted alkoxy, and R6 and R7 contain at least one trifluoromethyl group; if substituted, the substituent is alkyl, alkoxy or halogen.

4. The battery according to claim 1, characterized in that, The trifluoromethyl-substituted epoxide alkane compounds are selected from the compounds shown in Formula 4 below: R8-CF3 Formula 4 In Equation 4, R8 is selected from substituted or unsubstituted C. 3-10 Epoxyalkyl; if substituted, the substituent is halogen or C. 1-12 alkyl.

Citation Information

Patent Citations

  • LMFP (Li-Mn-Fe Phosphate) battery and electrolyte thereof

    CN108808089A

  • Electrolyte additive, electrolyte and lithium ion battery

    CN111682264A

  • Non-aqueous electrolytic solution additive for lithium secondary battery, and non-aqueous electrolytic solution for lithium secondary battery, and lithium secondary battery comprising same

    CN113678299A

  • Electrolyte for lithium secondary battery, and lithium secondary battery comprising same

    CN113692669A

  • Lithium ion battery non-aqueous electrolyte and application thereof

    CN113839093A